PERAN GURU KELAS DALAM MENUMBUHKAN MINAT LITERASI MENULIS PADA SISWA DI MADRASAH IBTIDAIYAH NURUL HUDA SEDENGANMIJEN KRIAN, SIDOARJO JAWA TIMUR (The Role Of The Class Teacher In Growing Interest In Writing Literature In Students at The Madrasah Ibtidaiyah Nurul Huda Sedenganmijen Krian, Sidoarjo East Java) - Muhamad Arif; Kusnul Munfa’ati; Anindya Galuh Winarti (Jurnal Ilmiah Didaktika, 2022)
This article explores facts about the role of classroom teachers foster students' interest in writing literacy. Several questions about writing literacy, covering how classroom teachers foster interest in writing literacy in students at Madrasah Ibtidaiyah Nurul Huda Sedenganmijen Krian, as well as what are the obstacles that class teachers in fostering interest in writing literacy at Madrasah Ibtidaiyah Nurul Huda Sedenganmijen Krian, from both focuses The problem is expected to provide detailed information about the growth of students' interest in writing literacy so that later it can be used as a reference to other elementary schools. This research uses a qualitative method with a case study approach, collecting data through interviews, observation, and documentation. The results of the study show that several classroom teachers have made breakthroughs, such as; familiarizing students with reading before starting the lesson, with a combination of class teachers giving students assignments to write personal stories in diaries. In addition, classroom teachers use several methods to foster students' interest in writing literacy, to be able to get maximum results. Synergy is a necessity in learning facilities such as the existence of learning media prepared by Madrasah Ibtidaiyah Nurul Huda Sendangmijen Krian, appropriate reading and writing literacy media, such as; Storybooks, picture stories, and fairy tales, wall magazines and children's encyclopedias, diaries, post it, film files (video).